Corrosion-resistant, antibacterial and anti-inflammatory biological coating as well as preparation method and application thereof
By forming a laminated biocoat on the surface of magnesium alloy implants, the problems of excessive degradation rate of magnesium alloy implants and bacterial infection-type inflammation are solved, and the long-term service of magnesium alloys in the human body is achieved and antibacterial and anti-inflammatory Effect.
Patent Information
- Application Number
- CN202411224440.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional magnesium alloy implants degrade too quickly in the human body, making it difficult to ensure an effective service period of 90 to 180 days, and are prone to bacterial infection-type inflammation and hinder the formation of new bone.
Biocoats with laminated structures, including inert layers and polymer layers, consisting of magnesium oxides and magnesium phosphates, the polymer layer contains chitosan and anti-inflammatory drugs, through microarc oxidation and leaching Prepare to form a corrosion-resistant, antibacterial and anti-inflammatory biological coating.
Extend the degradation rate of magnesium alloy implants, effectively prevent bacterial infection-type and sterile inflammation, improve the corrosion resistance and biocompatibility of the implants, and promote cell adsorption and growth.
Smart Images

Figure CN119158078A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional material preparation, and in particular relates to a corrosion-resistant, antibacterial and anti-inflammatory biological coating and a preparation method and application thereof. Background Art
[0002] With the acceleration of population aging, millions of people suffer fractures due to natural diseases and accidental injuries, making fracture reduction treatment a major clinical operation. Artificial bone implants are widely used to replace and fix injured bones to restore their normal physiological functions. Traditional implant materials are non-degradable. For some patients who only need short-term implants, a second operation is required to remove the implant after basic recovery, which increases the risk of surgery.
[0003] In order to solve the bottleneck problem faced by bone implants in clinical applications, magnesium alloys with good natural degradation ability have received widespread attention from scientific researchers in recent years. However, the application of magnesium alloys as degradable implant materials still has bottleneck problems. For example, its degradation rate is too fast, which makes it difficult to guarantee an effective service life of 90 to 180 days in the human physiological environment. In addition, during the tissue repair process of magnesium alloy implants, due to the lack of connective tissue, bacteria may adhere and colonize on the surface of magnesium alloy implants and proliferate rapidly, and eventually form a dense bacterial film. In severe cases, it may even cause bacterial infection-type inflammation, hinder the formation of new bone, and cannot cope with extreme bacterial infection inflammation and aseptic inflammation in the body. Summary of the invention
[0004] The purpose of the present invention is to provide a corrosion-resistant, antibacterial and anti-inflammatory biological coating, and a preparation method and application thereof. The biological coating provided by the present invention has a slow degradation rate and can effectively deal with bacterial infection-type inflammation and aseptic inflammation faced by implants when implanted into the human body.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a biological coating, comprising a stacked inert layer and a polymer layer; the inert layer comprises magnesium oxide and magnesium phosphate; the polymer layer comprises chitosan and anti-inflammatory drugs.
[0007] Preferably, the inert layer further comprises one or more of magnesium hydroxide, calcium hydroxide, calcium phosphate, magnesium calcium phosphate and calcium oxide; the molar ratio of magnesium element to oxygen element in the inert layer is 250-265:560-570; the molar ratio of magnesium element to calcium element in the inert layer is 250-265:85-100; the molar ratio of magnesium element to phosphorus element in the inert layer is 250-265:90-95.
[0008] Preferably, the mass ratio of chitosan to anti-inflammatory drug is 100-150:6-10.
[0009] Preferably, the thickness ratio of the inert layer to the polymer layer is 1:2-3.
[0010] The present invention also provides a method for preparing the biological coating described in the above scheme, comprising the following steps:
[0011] An inert layer is grown on the surface of a substrate by a micro-arc oxidation method, and then a polymer layer is grown on the surface of the inert layer by a leaching and pulling method, so as to obtain a biological coating on the surface of the substrate.
[0012] Preferably, the micro-arc oxidation method comprises the following steps: connecting a substrate to an anode of a power supply, connecting an electrolytic cell containing an electrolyte to a cathode of a power supply, wherein the substrate is not in direct contact with the electrolytic cell, and then placing the substrate in the electrolyte of the electrolytic cell for electroplating; the electrolyte comprises calcium hydroxide, sodium hexametaphosphate, an alkali metal compound and water; the power supply is a micro-arc oxidation power supply; the frequency of the micro-arc oxidation power supply is 100 to 500 Hz, the duty cycle is ±5% to ±20%, and the forward current is 0.4 to 0.8 A / cm 2 , negative current is 0~-0.5A / cm 2 .
[0013] Preferably, the leaching and pulling method comprises: immersing the substrate covered with the inert layer in an leaching solution and pulling, repeating the immersion and pulling, and then drying; the leaching solution comprises chitosan, an anti-inflammatory drug, acetic acid and water; the weight average molecular weight of the chitosan is 1×10 5 ~7×10 5 ; The concentration of chitosan in the extract is 10-15 g / L, and the concentration of the anti-inflammatory drug is 5-10 g / L; the pH value of the extract is 6.0-6.5.
[0014] Preferably, the immersion speed of the immersion pulling method is 5 to 10 mm / min, the pulling speed is 5 to 10 mm / min, the immersion time is 5 to 15 min, and the number of times is 3 to 6 times.
[0015] The present invention also provides the use of the biological coating described in the above scheme or the biological coating obtained by the preparation method described in the above scheme in artificial bone implants.
[0016] The present invention also provides a degradable implant, comprising a magnesium alloy implant and a biological coating loaded on the surface of the magnesium alloy implant; the biological coating is the biological coating described in the above scheme or the biological coating obtained by the preparation method described in the above scheme.
[0017] The present invention provides a biological coating. The biological coating provided by the present invention comprises a stacked inert layer and a polymer layer, wherein the inert layer has high chemical inertness, strong stability, and good corrosion resistance, but its porous structure cannot well block the corrosive medium, while the polymer layer is dense and highly chemically inert, and can fill the holes of the inert layer, thereby improving the overall corrosion resistance.
[0018] In addition, the polymer layer of the present invention contains chitosan loaded with anti-inflammatory drugs, which will degrade and release chitosan macromolecules and anti-inflammatory drug molecules when facing the slightly acidic environment caused by inflammation in the body; the positive charge carried by the chitosan macromolecule will come into contact with the negative charge on the surface of the bacterial cell membrane, causing the bacterial cell membrane to rupture and the bacteria to die; the anti-inflammatory drugs can inhibit the production of reactive oxygen in stimulated macrophages in the human body in a concentration-dependent manner, and have effective anti-inflammatory activity.
[0019] The biological coating provided by the present invention has excellent corrosion resistance, especially in a simulated body fluid environment, and can still maintain excellent corrosion resistance. It can also effectively deal with bacterial infection-type inflammation and aseptic inflammation faced by implants when implanted into the human body, and has good antibacterial and anti-inflammatory capabilities, protecting bone implants. The biological coating provided by the present invention has good biocompatibility and osteogenic ability, and is conducive to cell adsorption and growth.
[0020] The present invention also provides a method for preparing the biological coating of the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, high feasibility and prospect of large-scale application.
[0021] The present invention also provides the use of the biological coating described in the above scheme or the biological coating obtained by the preparation method described in the above scheme in artificial bone implants. The biological coating provided by the present invention can be used for artificial bone implants, especially magnesium alloy artificial bone implants, so that the magnesium alloy can effectively serve for 90 to 180 days in the human physiological environment, and can effectively deal with bacterial infection inflammation and aseptic inflammation faced by the implant when implanted into the human body.
[0022] The present invention also provides a degradable implant. The degradable implant provided by the present invention has excellent corrosion resistance, good antibacterial and anti-inflammatory capabilities, good biocompatibility and osteogenic ability, and is conducive to cell adsorption and growth. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 An electron microscope image of the biological coating provided by the present invention;
[0025] Figure 2 A physical diagram of a power source and an electrolytic cell used in an embodiment of the present invention;
[0026] Figure 3 A physical picture of an immersion coating apparatus used in an embodiment of the present invention;
[0027] Figure 4 The potentiodynamic polarization curves of the biological coatings of Example 1 and Comparative Examples 1 to 3 of the present invention;
[0028] Figure 5 It is a bacterial agar plate count diagram of the biological coating of Example 1 of the present invention and Comparative Examples 1 to 3;
[0029] Figure 6 The subcutaneous tissue immunological staining diagram of the biological coating of Example 1 and Comparative Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0030] The invention provides a biological coating, comprising a stacked inert layer and a polymer layer; the inert layer comprises magnesium oxide and magnesium phosphate; the polymer layer comprises chitosan and anti-inflammatory drugs.
[0031] The biological coating provided by the present invention comprises an inert layer; the inert layer preferably also comprises one or more of magnesium hydroxide, calcium hydroxide, calcium phosphate, magnesium calcium phosphate and calcium oxide.
[0032] In the present invention, the molar ratio of magnesium to oxygen in the inert layer is preferably 250-265:560-570, more preferably 255-260:563-567, and further preferably 257:565; the molar ratio of magnesium to calcium in the inert layer is preferably 250-265:85-100, more preferably 255-260:90-95, and further preferably 257:92; the molar ratio of magnesium to phosphorus in the inert layer is preferably 250-265:90-95, more preferably 255-260:91-94, and further preferably 257-259:92-93.
[0033] In the present invention, the magnesium oxide is preferably MgO; the magnesium hydroxide is preferably Mg(OH)2; the magnesium phosphate is preferably Mg3(PO4)2; the calcium hydroxide is preferably Ca(OH)2; the calcium phosphate is preferably Ca3(PO4)2; the magnesium calcium phosphate is preferably Mg2Ca(PO4)2; and the calcium oxide is preferably CaO.
[0034] The biological coating provided by the present invention comprises a polymer layer; the anti-inflammatory drug preferably comprises one or more of non-steroidal anti-inflammatory drugs and tannic acid, more preferably tannic acid; the non-steroidal anti-inflammatory drug preferably comprises one or more of dexamethasone and aspirin.
[0035] In the present invention, the mass ratio of chitosan to anti-inflammatory drugs is preferably 100-150:6-10, more preferably 120-140:7-9. The polymer layer provided by the present invention comprises 70-73 at% O, 21.0-24.0 at% C and 5.0-7.0 at% N.
[0036] In the present invention, the thickness ratio of the inert layer to the polymer layer is preferably 1:2-3, more preferably 1:2.5. In a specific embodiment of the present invention, the thickness of the inert layer is 3-4 microns, and the thickness of the polymer layer is 7-8 microns.
[0037] The biological coating provided by the present invention is as follows Figure 1 As shown. Figure 1 It can be seen that the inert layer ( Figure 1 The surface of a) is a porous structure with a pore diameter of less than 3 microns; the polymer layer ( Figure 1 b) The surface is dense and smooth, without obvious cracks and pores.
[0038] The present invention also provides a method for preparing the biological coating described in the above scheme, comprising the following steps:
[0039] An inert layer is grown on the surface of a substrate by a micro-arc oxidation method, and then a polymer layer is grown on the surface of the inert layer by a leaching and pulling method, so as to obtain a biological coating on the surface of the substrate.
[0040] The present invention adopts micro-arc oxidation method to grow an inert layer on the surface of the substrate. In the present invention, the substrate is preferably a magnesium alloy; the substrate is preferably pretreated before use.
[0041] In the present invention, the pretreatment is preferably cleaning; the cleaning preferably includes acetone cleaning, ethanol cleaning and water washing in sequence; the acetone cleaning, ethanol cleaning and water washing are preferably ultrasonic cleaning; the power of the ultrasonic cleaning is preferably 220-260W, more preferably 240-250W.
[0042] In the present invention, the number of acetone cleaning is preferably 5 to 10 times, more preferably 7 to 8 times; the total time of acetone cleaning is preferably 15 to 20 minutes, more preferably 17 minutes; after acetone cleaning, it is preferred to further include blowing dry the substrate surface; the blowing dry is preferably nitrogen blowing dry.
[0043] The number of ethanol cleaning is preferably 5 to 10 times, more preferably 6 to 8 times; the total time of the ethanol cleaning is preferably 15 to 20 minutes, more preferably 17 minutes; after the ethanol cleaning, it is preferred that the substrate surface is blown dry; the blow drying is preferably nitrogen blow drying.
[0044] The water used for washing is preferably deionized water; the number of times of washing is preferably 2 to 3 times, more preferably 3 times; the total time of washing is preferably 15 to 20 minutes, more preferably 17 minutes; after washing, the substrate surface is preferably blown dry; the blow drying is preferably nitrogen blow drying.
[0045] In the present invention, the micro-arc oxidation method preferably includes the following steps: connecting the substrate to the anode of the power supply, connecting the electrolytic cell containing the electrolyte to the cathode of the power supply, the substrate is not in direct contact with the electrolytic cell, and then placing the substrate in the electrolyte of the electrolytic cell for electroplating.
[0046] In the present invention, the electrolyte preferably includes calcium hydroxide, sodium hexametaphosphate, an alkali metal compound and water; the alkali metal compound is preferably potassium fluoride or sodium hydroxide; the concentration of calcium hydroxide in the electrolyte is preferably 1-1.5 g / L, more preferably 1.2 g / L, and the concentration of sodium hexametaphosphate is preferably 4-6 g / L, more preferably 5 g / L; when the alkali metal compound is potassium fluoride, the concentration of potassium fluoride is preferably 7.5-8 g / L, more preferably 7.7-7.9 g / L; when the alkali metal compound is sodium hydroxide, the concentration of sodium hydroxide is preferably 4-8 g / L, more preferably 5-7 g / L; the water is preferably deionized water.
[0047] In the present invention, the power source is preferably a micro-arc oxidation (MAO) power source; the frequency of the MAO power source is preferably 100 to 500 Hz, more preferably 500 Hz, the duty cycle is preferably ±5% to ±20%, more preferably ±10%, and the forward current is preferably 0.4 to 0.8 A / cm 2 , more preferably 0.6A / cm 2 The negative current is preferably 0 to -0.5A / cm 2 , more preferably -0.2A / cm 2 .
[0048] In the present invention, the electroplating preferably adopts a constant current mode; the working time of the electroplating is preferably 2 to 30 minutes, more preferably 5 minutes; the electroplating is preferably carried out under stirring conditions; the stirring rate is preferably 2 to 4 rev / sec, more preferably 2 rev / sec.
[0049] After the inert layer is grown (obtaining a substrate covered with the inert layer), the present invention uses an immersion-extraction coating method to grow a polymer layer on the surface of the inert layer to obtain a biological coating on the surface of the substrate. In the present invention, the equipment for the immersion-extraction coating method is preferably an immersion-extraction coating apparatus.
[0050] In the present invention, the leaching and pulling method is preferably: immersing the substrate covered with the inert layer in a leaching solution and pulling it, repeating the immersion and pulling, and then drying.
[0051] In the present invention, the immersion pulling method preferably fixes the substrate covered with the inert layer on the cantilever of the immersion pulling coating apparatus. The present invention adjusts the cantilever height, pulling height and immersion height so that the substrate is completely immersed in the leaching solution during each immersion pulling process.
[0052] In the present invention, the extract preferably comprises chitosan, anti-inflammatory drugs, acetic acid and water; the weight average molecular weight of the chitosan is preferably 1×10 5 ~7×10 5 , more preferably 1×10 5 ~4×10 5 .
[0053] In the present invention, the concentration of chitosan in the extract is preferably 10-15 g / L, more preferably 12-14 g / L, the mass concentration of acetic acid is preferably 1%, the concentration of the anti-inflammatory drug is preferably 5-10 g / L, more preferably 5-8 g / L; the pH value of the extract is preferably 6.0-6.5, more preferably 6.0.
[0054] In the present invention, the preparation method of the extract is preferably: premixing acetic acid solution and chitosan to obtain a premixed solution, adjusting the pH value of the premixed solution to 6.0-6.5 to obtain a chitosan solution, and then mixing the chitosan solution with an anti-inflammatory drug.
[0055] In the present invention, the regulating solution for regulating the pH value of the premixed solution is preferably a sodium hydroxide solution; and the concentration of the sodium hydroxide solution is preferably 1 mol / L.
[0056] In the present invention, the immersion speed of the immersion pulling method is preferably 5-10 mm / min, more preferably 10 mm / min, the pulling speed is preferably 5-10 mm / min, more preferably 8-10 mm / min, the immersion time is preferably 5-15 min, more preferably 5 min, and the number of times is preferably 3-6 times, more preferably 6 times.
[0057] In the present invention, the drying temperature is preferably 24-37° C., more preferably 37° C.; the drying equipment is preferably an oven.
[0058] The present invention also provides the use of the biological coating described in the above scheme or the biological coating obtained by the preparation method described in the above scheme in artificial bone implants.
[0059] The biological coating provided by the present invention can be used for artificial bone implants, especially magnesium alloy artificial bone implants, so that the magnesium alloy can effectively serve for 90 to 180 days in the human physiological environment, and can effectively deal with bacterial infection inflammation and aseptic inflammation faced by the implant when implanted into the human body.
[0060] The present invention also provides a degradable implant, comprising a magnesium alloy implant and a biological coating loaded on the surface of the magnesium alloy implant; the biological coating is the biological coating described in the above scheme or the biological coating obtained by the preparation method described in the above scheme.
[0061] The degradable implant provided by the present invention has excellent corrosion resistance, good antibacterial and anti-inflammatory capabilities, as well as good biocompatibility and osteogenic ability, and is conducive to cell adsorption and growth.
[0062] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0063] Example 1
[0064] Substrate pretreatment: The magnesium alloy was ultrasonically cleaned by placing it in acetone, ethanol and deionized water for 15 minutes each, and then taken out. Each step was dried with nitrogen to obtain a substrate with a clean surface.
[0065] Prepare electrolyte: put 3.6g of calcium hydroxide, 12g of sodium hexametaphosphate, and 24g of potassium fluoride into 3L of deionized water, stir until completely dissolved, obtain electrolyte, and introduce into the electrolytic cell.
[0066] Preparation of inert layer: Connect the treated magnesium alloy substrate to a MAO power source (such as Figure 2 a) anode and placed in an electrolytic cell (as shown in Figure 2 b) is immersed in the electrolyte, and the electrolytic cell is connected to the cathode of the MAO power supply. During this process, the magnesium alloy is maintained in non-direct contact with the electrolytic cell; during the preparation process, the electrolyte in the electrolytic cell is stirred at a stirring rate of 2 rpm; the MAO power supply uses a constant current mode with a frequency of 500 Hz, a duty cycle of ±10%, a constant forward current of 0.6 A / cm, a negative current of -0.2 A / cm, and a working time of 5 minutes to obtain an oxide-coated substrate, which is ultrasonically cleaned with deionized water for 15 minutes as a substrate for immersion pulling; the content of each element in the oxide layer is Mg (25.0 at.%), O (56.5 at.%), Ca (8.9 at.%), and P (9.3 at.%).
[0067] Pulling and impregnation: Prepare chitosan solution. In this example, the molecular weight of the chitosan solution is 10×10 4 chitosan powder, add 1g of chitosan powder to every 99mL of 1.0% acetic acid solution, stir the solution until the chitosan powder is completely dissolved, increase the pH from about 3.0 to 6.0-6.5 by adding sodium hydroxide (1mol / L) solution, add 0.5g of tannic acid to every 100mL of chitosan solution, stir until the tannic acid and chitosan solution are evenly mixed; then, fix the substrate covered with the inert layer on an immersion coating apparatus (such as Figure 3 The cantilever (as shown) was vertically immersed in the chitosan solution for 5 minutes, and then pulled up at a constant speed of 10 mm / min to prepare a polymer layer. This process was repeated 6 times to obtain a substrate covered with a biological coating.
[0068] Drying: After the coating is completed, the substrate coated with the bio-coating is placed in an oven at 37° C. to dry to obtain a degradable implant; the composition of the polymer layer: Mg (1.1 at.%), O (71.8 at.%), C (21.4 at.%), N (5.2 at.%).
[0069] Performance Testing
[0070] The degradable implant was immersed in SBF simulated body fluid for 24 hours for corrosion resistance test. The corrosion current density of the degradable implant was 4.9301×10 -9 A / cm 2 The electrochemical impedance value is 2×10 6 Ωcm 2 .
[0071] Staphylococcus aureus and Escherichia coli were cultured at 1×10 6 cells / cm 2 The initial density of 10 ...
[0072] The degradable implants were subcutaneously implanted into C57BL / 6 mice to evaluate the in vivo anti-inflammatory effect of the degradable implants and their histological effects. The results of immunological staining of the tissues surrounding the degradable implants showed that tumor necrosis factor-α (IF-1β) was less expressed and the in vivo anti-inflammatory effect was significant.
[0073] Example 2
[0074] The preparation method of this embodiment is the same as that of embodiment 1, except that when preparing the inert layer, the forward constant current is adjusted to 0.4 A / cm 2 The content of each element in the obtained inert layer is: Mg (25.6 at.%), O (54.2 at.%), Ca (8.8 at.%), P (8.9 at.%).
[0075] The antibacterial and anti-inflammatory properties of the product of this embodiment are substantially the same as those of embodiment 1, but the corrosion resistance is slightly worse.
[0076] Example 3
[0077] The preparation method of this embodiment is the same as that of embodiment 1, except that, when preparing the polymer layer, 1.5 g of chitosan powder is added to every 99 mL of 1.0% acetic acid solution. The content of each element in the obtained polymer layer is: Mg (1.1 at.%), O (71.8 at.%), C (22.6 at.%), N (5.7 at.%).
[0078] The performance of the product in this embodiment is substantially the same as that in embodiment 1.
[0079] Comparative Example 1
[0080] Compared with the magnesium alloy substrate, the magnesium alloy was immersed in SBF simulated body fluid for 24 hours and then subjected to corrosion resistance test. The corrosion current density of the magnesium alloy was 2.2185×10 -4 A / cm 2 The electrochemical impedance value is 2×10 2 Ωcm 2 The apoptosis rate of Escherichia coli and Staphylococcus aureus cultured on the surface of magnesium alloy reached 62.4%; after magnesium alloy was subcutaneously implanted into mice, the immunological staining of the surrounding tissues showed that tumor necrosis factor-α (IF-1β) was expressed more.
[0081] Comparative Example 2
[0082] Compared with the substrate covered with an inert layer, that is, the product obtained by the inert layer preparation step in Example 1. The substrate covered with the inert layer was immersed in SBF simulated body fluid for 24 hours and then subjected to corrosion resistance test. The corrosion current density of the substrate covered with the inert layer was 9.1023×10 -8 A / cm 2 The electrochemical impedance value is 1.4×10 5 Ωcm 2 Most of the Escherichia coli and Staphylococcus aureus cultured on the surface of the substrate covered with the inert layer grew well, and the apoptosis rate was only 2.1%; after the substrate covered with the inert layer was subcutaneously implanted into mice, the immunological staining of the surrounding tissues showed that tumor necrosis factor-α (IF-1β) was expressed more.
[0083] Comparative Example 3
[0084] Compared with the substrate covered with the polymer layer, the inert layer preparation step is omitted in Example 1, and only the immersion and pulling step is retained; the substrate covered with the polymer layer is immersed in SBF simulated body fluid for 24 hours and then subjected to corrosion resistance test. The corrosion current density of the substrate covered with the polymer layer is 1.8976×10 -6 A / cm 2 The electrochemical impedance value is 2.4×10 4 Ωcm 2 Most of the Escherichia coli and Staphylococcus aureus cultured on the surface of the polymer-coated substrate were apoptotic, with an apoptosis rate of about 92%; after the polymer-coated substrate was subcutaneously implanted into mice, the immunological staining of the surrounding tissues showed that tumor necrosis factor-α (IF-1β) was highly expressed.
[0085] Electrochemical tests were performed on Example 1 and Comparative Examples 1 to 3. The test method was as follows: the working area of the sample to be tested was 1 cm 2 The corrosion medium is a sodium chloride solution with a mass concentration of 0.9%. The test adopts a three-electrode system, with the sample to be tested as the working electrode, the Pt electrode as the auxiliary electrode, and the saturated calomel electrode (SCE) as the reference electrode. The working electrode and the reference electrode are connected by a salt bridge. The test is carried out at the open circuit potential (OCP) of the sample to be tested, the sine wave potential amplitude is 10mV, the frequency scanning range is 100~10mHz, the dynamic potentiodynamic polarization curve test scanning rate is 0.50mV / s, and the scanning range is ±250mV (vsOCP). The results are as follows: Figure 4 As shown. Figure 4 It can be seen from the potentiodynamic polarization curve that a single inert layer can reduce the corrosion current density of the magnesium alloy by 4 orders of magnitude, while the biological coating doped with the anti-inflammatory drug tannic acid can reduce the corrosion current density of the magnesium alloy by 5 orders of magnitude, showing the best corrosion resistance.
[0086] The bacterial agar plate count results of Example 1 and Comparative Examples 1 to 3 are as follows: Figure 5 Compared with the bare magnesium alloy and the magnesium alloy covered with only an inert layer in Comparative Examples 1-2, the substrate containing the polymer layer (Example 1 and Comparative Example 3) has the least number of residual colonies on the agar plate, showing better bactericidal ability.
[0087] The immunological staining images of subcutaneous tissues of Example 1 and Comparative Examples 1 to 3 are as follows: Figure 6 As shown. Figure 6 It can be seen that the area of the brown part can be used to represent the expression level of the pro-inflammatory factor 1L-1β. In the figure, the degradable implant doped with the anti-inflammatory drug tannic acid (Example 1) has the smallest brown part area, indicating that the pro-inflammatory factors in the tissue surrounding the degradable implant are the least and the anti-inflammatory effect is the strongest.
[0088] It can be seen from the above examples that the biological coating provided by the present invention has good corrosion resistance, can protect implants, slow down their degradation rate, and can effectively deal with bacterial infection-type inflammation and aseptic inflammation faced by implants when implanted into the human body.
[0089] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A biological coating, characterized in that: comprising a stacked inert layer and a polymer layer; The inert layer includes magnesium oxide and magnesium phosphate; The polymer layer includes chitosan and an anti-inflammatory drug.
2. The bio-coating according to claim 1, characterized in that The inert layer also includes one or more of magnesium hydroxide, calcium hydroxide, calcium phosphate, magnesium calcium phosphate and calcium oxide; the molar ratio of magnesium element to oxygen element in the inert layer is 250-265:560-570; the molar ratio of magnesium element to calcium element in the inert layer is 250-265:85-100; the molar ratio of magnesium element to phosphorus element in the inert layer is 250-265:90-95.
3. The bio-coating according to claim 1, characterized in that The mass ratio of the chitosan to the anti-inflammatory drug is 100-150:6-10.
4. The biological coating according to claim 1 or 2, characterized in that The thickness ratio of the inert layer to the polymer layer is 1:2-3.
5. The method for preparing the biological coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: An inert layer is grown on the surface of a substrate by a micro-arc oxidation method, and then a polymer layer is grown on the surface of the inert layer by a leaching and pulling method, so as to obtain a biological coating on the surface of the substrate.
6. The preparation method according to claim 5, characterized in that: The micro-arc oxidation method comprises the following steps: connecting a substrate to an anode of a power supply, connecting an electrolytic cell containing an electrolyte to a cathode of a power supply, wherein the substrate is not in direct contact with the electrolytic cell, and then placing the substrate in the electrolyte of the electrolytic cell for electroplating; the electrolyte comprises calcium hydroxide, sodium hexametaphosphate, an alkali metal compound and water; The power supply is a micro-arc oxidation power supply; the frequency of the micro-arc oxidation power supply is 100-500 Hz, the duty cycle is ±5%-±20%, and the forward current is 0.4-0.8 A / cm 2 , negative current is 0~-0.5A / cm 2 .
7. The preparation method according to claim 5, characterized in that: The leaching and pulling method comprises: immersing the substrate covered with the inert layer in a leaching solution and pulling it, repeating the immersion and pulling, and then drying; The extract comprises chitosan, anti-inflammatory drugs, acetic acid and water; the weight average molecular weight of the chitosan is 1×10 5 ~7×10 5 ; The concentration of chitosan in the extract is 10-15 g / L, and the concentration of the anti-inflammatory drug is 5-10 g / L; the pH value of the extract is 6.0-6.
5.
8. The preparation method according to claim 5 or 7, characterized in that: The immersion speed of the immersion pulling method is 5 to 10 mm / min, the pulling speed is 5 to 10 mm / min, the immersion time is 5 to 15 minutes, and the number of times is 3 to 6 times.
9. Use of the biological coating according to any one of claims 1 to 4 or the biological coating obtained by the preparation method according to any one of claims 5 to 8 in artificial bone implants.
10. A degradable implant, characterized in that: It comprises a magnesium alloy implant and a biological coating loaded on the surface of the magnesium alloy implant; the biological coating is the biological coating according to any one of claims 1 to 4 or the biological coating obtained by the preparation method according to any one of claims 5 to 8.
Citation Information
Patent Citations
Multifunctional compound drug eluting slow-release system and preparation method thereof
CN103705294A
Preparation method of medical pure magnesium surface electrophoretic deposition carried bone growth inducing traditional Chinese medicine coating
CN106676608A
Preparation method of medical drug-release functional coating applied to surface of magnesium alloy
CN110639056A
Preparation method of composite coating for improving corrosion resistance and antibacterial property of magnesium alloy
CN111842086A
Medical magnesium alloy barrier membrane for alveolar bone defect repair and preparation method of medical magnesium alloy barrier membrane
CN113730655A
Cited By
Lantern-imitating frame internal fixing system with intelligent responsive coating and preparation method of lantern-imitating frame internal fixing system
CN120983715A
